2010
DOI: 10.1179/174328409x428927
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of new copper matrix composite reinforced by β-eucryptite particulates

Abstract: Cu matrix composites with different volume fraction of Ag coated β-eucryptite particulates were successfully fabricated by powder metallurgy method. Low thermal expansion coefficient and high thermal conductivity were attained simultaneously in the new Cu matrix composite. The microstructure of β-eucryptite–Cu composite was studied by scanning electron microscope and transmission electron microscope. The thermophysical properties of β-eucryptite–Cu composites were analysed by means of thermal dilatometer and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In addition, the compressive stress and the tensile stress are simultaneously induced on the SBT particles and on the Cu matrix, respectively, when the composite is cooled from a high temperature because the CTE of the SBT particles is lower than that of the Cu matrix 14 15 . The tensile stress acting on the matrix can be relaxed upon heating, and K m is much smaller than K p in the SBT/Cu composite; therefore, it can be concluded that the CTE of the composite decreases during this process on the basis of Equation (1) and our previous studies 16 17 25 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the compressive stress and the tensile stress are simultaneously induced on the SBT particles and on the Cu matrix, respectively, when the composite is cooled from a high temperature because the CTE of the SBT particles is lower than that of the Cu matrix 14 15 . The tensile stress acting on the matrix can be relaxed upon heating, and K m is much smaller than K p in the SBT/Cu composite; therefore, it can be concluded that the CTE of the composite decreases during this process on the basis of Equation (1) and our previous studies 16 17 25 .…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, many studies have investigated negative-CTE ceramics to reinforce MMCs with a low CTE and high TC, such as β-eucryptite (AlLiSiO 4 )14151617 and ZrW 2 O 8 181920. However, the CTE of β-eucryptite (approximately −0.7 × 10 −6  K −1 ) is not as low as expected and microcracks are easily formed in the bulk β-eucryptite ceramics due to its poor strength.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A more promising approach to lower the braze CTE is to introduce a negative thermal expansion (NTE) filler material, which contracts upon heating [32][33][34][35][36][37][38]. A practically important NTE material is LiAlSiO 4 , which has an anisotropic CTE (α a = 8.21 × 10 -6 K -1 and α c = -17.6 × 10 -6 K -1 , 0-1000 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Xue et al [35][36][37][38] successfully employed LiAlSiO 4 particles to lower the thermal expansion of Al and Cu matrix composites. The same group also showed that the wettability between Cu and LiAlSiO 4 can be improved by coating the LiAlSiO 4 particles with Ag [38]. Thus, these findings suggest that LiAlSiO 4 is suitable for lowering the thermal expansion of Ag-Cu composite brazes.…”
Section: Introductionmentioning
confidence: 99%